A phase 2 clinical trial assessing the efficacy and safety of pembrolizumab and radiotherapy in patients with metastatic triple‐negative breast cancer. Issue 4 (20th November 2019) - Ho, Alice Y.; Barker, Christopher A.; Arnold, Brittany B.; Powell, Simon N.; Hu, Zishuo I.; Gucalp, Ayca; Lebron‐Zapata, Lizza; Wen, Hannah Y.; Kallman, Cindy; D'Agnolo, Alessandro; Zhang, Zhigang; Flynn, Jessica; et al.
Abstract : Background: The current study was conducted to evaluate the efficacy and safety of pembrolizumab‐mediated programmed cell death protein 1 inhibition plus radiotherapy (RT) in patients with metastatic triple‐negative breast cancer who were unselected for programmed death‐ligand 1 expression. Methods: The current study was a single‐arm, Simon 2‐stage, phase 2 clinical trial that enrolled a total of 17 patients with a median age of 52 years (range, 37‐73 years). An RT dose of 3000 centigrays (cGy) was delivered in 5 daily fractions. Pembrolizumab was administered intravenously at a dose of 200 mg within 3 days of the first RT fraction, and then every 3 weeks ± 3 days until disease progression. The median follow‐up was 34.5 weeks (range, 2.1‐108.3 weeks). The primary endpoint of the current study was the overall response rate (ORR) at week 13 in patients with unirradiated lesions measured using Response Evaluation Criteria in Solid Tumors (RECIST; version 1.1). Secondary endpoints included safety and progression‐free survival. Exploratory objectives were to identify biomarkers predictive of ORR and progression‐free survival. Results: The ORR for the entire cohort was 17.6% (3 of 17 patients; 95% CI, 4.7%‐44.2%), with 3 complete responses (CRs), 1 case of stable disease, and 13 cases of progressive disease. Eight patients died prior to week 13 due to disease progression. Among the 9 women assessed using RECIST version 1.1 at week 13, 3 (33%) achieved a CR, with a 100% reduction in tumor volume outside of the irradiated portal. The CRs were durable for 18 weeks, 20 weeks, and 108 weeks, respectively. The most common grade 1 to 2 toxicity (assessed according to the National Cancer Institute Common Terminology Criteria for Adverse Events, version 4.0) was dermatitis (29%). Four grade 3 adverse events were attributed to pembrolizumab: fatigue, lymphopenia, and infection. No were no grade 4 adverse events or treatment‐related deaths reported. Conclusions: The combination of pembrolizumab and RT was found to be safe and demonstrated encouraging activity in patients with poor‐prognosis, metastatic, triple‐negative breast cancer who were unselected for programmed death‐ligand 1 expression. Larger clinical trials of checkpoint blockade plus RT with predictive biomarkers of response are needed. Abstract : The current phase 2, multi‐institutional study evaluates whether the combination of the programmed cell death protein 1 immune checkpoint inhibitor pembrolizumab and radiotherapy (RT) is safe and effective in patients with metastatic triple‐negative breast cancer (mTNBC). Among 17 women in the current study with pretreated mTNBC who received pembrolizumab and RT, the combination appears safe and demonstrates an encouraging signal within a poor‐prognosis population, indicating that further study of the combination is warranted.